The impact of tropical cyclones on fishing activities in the Philippines - Ilan Noy; Miloud Lacheheb; Madhavi Pundit (Asian Development Bank (ADB), 2023)
In this paper, we identify the main fishing grounds and track the response of fishing vessels' activity to tropical cyclones (TCs) in the Philippines' Exclusive Economic Zone during 2012. We use satellite imagery from the National Oceanic and Atmospheric Administration to locate fishing vessels and identify the main fishing grounds; in conjunction with data on TCs' speed and trajectory from the International Best Track Archive for Climate Stewardship database. We use kernel density functions to identify fishing grounds and Vector Generalized Linear Model and Bayesian Time-Varying Parameter to assess the impact of TC speed on the location of fishing vessels during and after the TC. Our quantifications reveal the overall negative impact of TCs on the number of active boats during and 2 days after the TC. The fishing grounds located within the Sibuyan Sea, Visayan Sea, and Panay Gulf are the most affected areas. Daily reduction in the commercial fishing production in Western Visayas alone for every day a TC passed through was estimated at 7,800 tons per day, affecting more than 188,000 families.
Keywords: Q22; Q54; 330; fisheries; Philippines; tropical cyclone; satellite imagery; economic impact